Panchayati Raj Institutions and Women's Land Ownership: Learning from Gujarat. (July 2015) - Vasavada, Shilpa; Rajgor, Meena; Ganguly, Varsha
Women's right to property, especially agricultural land, is positively linked to a better quality of life as well as welfare of the family, gender equality and reducing their vulnerability to domestic violence and their house chore drudgeries. Nonetheless, ensuring women's rights to land has remained a challenge, which mainly revolves around implementation and enforcement of various laws and policies across many countries; India is no exception. This article shares various initiatives of a state-level network and its impact on women's land ownership in Gujarat state of India. A major learning is to capture and influence the 'middle space', that is, a space between social action at the grassroots and changes in policy is very important for ensuring women's land ownership. The larger question is 'whether these experiences and learning are trendsetting' in a given local governance (Panchayati Raj) and land administration system, which has to be moved by a gamut of grassroots' initiatives and grabbing opportunities provided by state government initiatives for women.